2021
DOI: 10.1007/s00586-021-06886-1
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical anatomy of the lumbar sinuvertebral nerve with regard to discogenic low back pain and review of literature

Abstract: Purpose Lumbar discogenic diffuse pain is still not understood. Authors describe the sinuvertebral nerve (SVN) as one possible cause. Body-donor studies are rare and controversial. Therefore, the aim was to revisit the origin, course and distribution in a body-donor study. Methods Six lumbar blocks (3 female, 3 male) aged between 59 and 94 years were dissected. After removal of the back muscles, lamina, dura mater and cauda equina, the anterior vertebral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 36 publications
(118 reference statements)
0
4
0
Order By: Relevance
“…IVDD is known for the underlying cause of DLBP [19], and it often leads to the following: (1) mechanical changes: physiologically, the adult intervertebral disc is almost devoid of blood vessels, and only small vessels from the segmental arterial branches penetrate around the AF, mostly at the anterior and posterior edges of the disc. Tese innate anatomical weaknesses cause the lumbar intervertebral discs to undergo extreme biomechanical stimulation, and over time, the stress leads to the less elastic NP crossing the weakened AF [20]; (2) pain changes: the level of pain depends on the pain-sensitive tissues of the spinal canal-AF of the disc, the posterior longitudinal ligament, and the SVN endings distributed on the surface of the dura [21]; and (3) chemical changes: the locally injured intervertebral disc transforms from being self-contained to contact with the outside world and due to the antigenic properties of intervertebral disc tissues, an immune-infammatory response is triggered, resulting in an autoimmune reaction in the disc and chronic infammation and LBP [22]. Te targeted RFT therapy is a common method for the treatment of DLBP due to IVDD [23].…”
Section: Discussionmentioning
confidence: 99%
“…IVDD is known for the underlying cause of DLBP [19], and it often leads to the following: (1) mechanical changes: physiologically, the adult intervertebral disc is almost devoid of blood vessels, and only small vessels from the segmental arterial branches penetrate around the AF, mostly at the anterior and posterior edges of the disc. Tese innate anatomical weaknesses cause the lumbar intervertebral discs to undergo extreme biomechanical stimulation, and over time, the stress leads to the less elastic NP crossing the weakened AF [20]; (2) pain changes: the level of pain depends on the pain-sensitive tissues of the spinal canal-AF of the disc, the posterior longitudinal ligament, and the SVN endings distributed on the surface of the dura [21]; and (3) chemical changes: the locally injured intervertebral disc transforms from being self-contained to contact with the outside world and due to the antigenic properties of intervertebral disc tissues, an immune-infammatory response is triggered, resulting in an autoimmune reaction in the disc and chronic infammation and LBP [22]. Te targeted RFT therapy is a common method for the treatment of DLBP due to IVDD [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect has been reported to be unpredictable. Quinones et al ( 30 ) found that The SVN had a recurrent course below the inferior vertebral notch and suggest blocking the SVN at the level of the inferior vertebral notch of two adjacent segments to obtain good therapeutic effect. Breemer et al ( 31 ) believed that lower lumbar discogenic pain is presumably mediated segmentally via the somatic SVN root and non-segmentally through the autonomic SVN root; targeting only the non-segmental pathway may provide incomplete pain reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Lower back pain is also one of the most common symptoms leading to lumbar spinal fusion [ 67 , 101 ]. Sinuvertebral and basivertebral neuropathy were described by several authors as the one of the key contributing factors for discogenic lower back pain [ 29 , 43 , 44 , 80 , 88 ]. In this narrative review, we discussed the pathophysiology and management of sinuvertebral and basivertebral neuropathy.…”
Section: Introductionmentioning
confidence: 99%